2020
DOI: 10.3389/fpls.2020.01223
|View full text |Cite
|
Sign up to set email alerts
|

The Resistant Soybean-Aphis glycines Interaction: Current Knowledge and Prospects

Abstract: Soybean aphids (Aphis glycines Matsumura) are invasive insect pests of soybean, and they cause significant yield losses. Resistance to soybean aphids is conferred by Resistance to Aphis glycines (Rag) genes. Since the first discovery of aphid-resistant soybean genotypes in 2004, several studies have attempted to characterize Rag genes from aphid-resistant soybean genotypes. To date, 12 Rag genes and four quantitative trait loci for aphid resistance have been reported on soybean chromosomes 07, 08, 13, 16, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 77 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Other aphid resistance genes identified are linked to both antibiosis and antixenosis components, such as the Rag genes in soybean (Glycine max) that confer resistance to the soybean aphid (Aphis glycines). Of the12 Rag genes identified, Rag1 and Rag5 are two R genes that mediate antibiosis and antixenosis components [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Other aphid resistance genes identified are linked to both antibiosis and antixenosis components, such as the Rag genes in soybean (Glycine max) that confer resistance to the soybean aphid (Aphis glycines). Of the12 Rag genes identified, Rag1 and Rag5 are two R genes that mediate antibiosis and antixenosis components [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The association of aphid resistance in soybean with phytochemical defenses is not as common as it is with 5 resistance genes ( Rag 1 - Rag 5 ) that are correlated with negative effects to biology and behaviour [ 31 ]. A recent review of the potential mechanisms of Rag gene action summarized that the induction of these genes is related to secondary metabolite production, but the metabolites (isoflavonoids, phenolics, and others) levels were not correlated with changes in aphid feeding behavior in order to advance knowledge on host plant resistance [ 32 ]. Currently, there is no known genetic association with resistance to TSSM so the cultivars screened in the present research were compared by leaf chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The use of detached leaves has been proposed as a more rapid and practical assay to screen germplasm for resistance to aphids. Several studies have shown no significant differences in aphid performance on detached leaves than intact plants, but these studies used only susceptible plants (MacKinnon, 1961;Nam and Hardie, 2012;Soffan and Aldawood, 2014;Li and Akimoto, 2018). When detached leaf assays are performed with resistant plants, contrasting results are observed.…”
Section: Discussionmentioning
confidence: 99%